Dependence on Technology and Decline in Social Interaction: What's Missing? - Loso Judijanto; Sara Hussain; Sidi Mohamed Toure (Journal of Social Science Utilizing Technology, 2025)
Background. The increasing integration of technology into everyday life has transformed how individuals communicate, work, and engage with the world. While digital platforms offer efficiency and global connectivity, growing dependence on technology has been linked to a noticeable decline in face-to-face social interaction. This phenomenon raises important questions about what may be missing in the quality and depth of human relationships in technologically saturated environments. Purpose. This study aims to investigate the relationship between technological dependence and the decline of in-person social interaction, focusing on the underlying psychological, behavioral, and cultural factors that contribute to this shift. The research also explores how different age groups perceive and experience social connectivity in the digital age. Method. Using a mixed-methods approach, the study combines quantitative surveys involving 400 respondents from diverse demographic backgrounds with qualitative interviews of 20 individuals across three age groups: youth, adults, and seniors. Data analysis included statistical correlations and thematic coding to identify patterns in social behavior and emotional well-being. Results. Results reveal that increased screen time correlates with reduced quality of social engagement, particularly among younger participants. Many respondents reported feelings of isolation despite being digitally connected. The findings suggest that while technology facilitates communication, it may inadvertently replace more meaningful, emotionally resonant interactions. Conclusion. The study concludes that over-reliance on technology can diminish key aspects of human connection such as empathy, presence, and shared experience. Reintegrating intentional social practices into daily life may be essential to restoring balance between digital convenience and emotional fulfillment.